(3eHGOF GdJShjb hGdJQhjLs - (3GHQGgje(B, (3GdTQjas ((3YeGf(B:s (3OGQ CSGeI ddfTQ h GdJhRjY,s, 2006)
(3jVe GdJShjb, JMdjd GdShb GOGQI GdJShjb, CgOGa GdJShjb, KbGaI GdJShjb, fJhjY eUOQ GdONd, af GdGbfGY hGdJaGhV aj GdJShjb, GdJNWjW GdTGed dCHMGK GdShb, cja Jchf efGaSG aj GdShb, cja Jchf eHOYG, CSGdjH GHQGe GdUabI, CfhGY GdRHGFf, OQGSI GdRHhf ef NdGd GdGjeGAGJ, GdOYGjI hGdGYdGf, GOGQI GdJShjb Sdhc GdeSJgdc, GdeaGgje GdGLJeGYjI, GfLGR GdfTGW GdJShjbj GdeTJQc, GOGQI GdJQhjL, cja JUfY NWI JShjbjI eMceI, cja JSJKeQ hbJc dJchf eShbG LjOG, KbGaI GdeSJgdcs
(3HjHdjhZQGajG(B: (3U(B.168s
Keywords: (3GdGTgGQs; (3GdGYdGfs; (3GdJQhjLs; (3GdJShjbs